How Community Education Tools Facilitated Understanding of the ASPIRE Vaginal Ring Study: Kampala Experience - Ndawula, Patrick; Nakyanzi, Teopista; Etima, Juliane; Kabwigu, Samuel; Matovu, Flavia K.; Nanziri, Sophie C.; Kemigisha, Doreen; Nanyonga, Stella; White, Rhonda; Cokley, Cheryl; Nakabiito, Clemesia (AIDS Research and Human Retroviruses, 2014)
UNAIDS Good participatory practice guidelines for biomedical HIV prevention trials recommends that sufficient trial information, such as study objectives, procedures, risks, benefits, and what is expected of participants, is provided for potential participants to make informed decisions. We describe how ASPIRE community education tools increased study awareness and enabled literacy regarding research, reproductive health, family planning, and HIV prevention.
Keywords: Community Education Tools; ASPIRE Vaginal Ring Study; Kampala